2021
DOI: 10.1021/acsabm.1c00451
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired, Injectable Polyurethane Tissue Adhesives Demonstrate In Situ Gel Formation under Mild Conditions

Abstract: Tissue adhesives are widely desired in surgical wound closure and interfacial modification of medical devices. However, poor adhesive strength, low mechanical compliance, high costs, and biotoxicity of traditional adhesives limit their biomedical applications. In this work, we fabricated a class of mussel-inspired polyurethane adhesives (MPUAs) with robust properties, including in situ gel formation under mild conditions, accommodation of intricate wounds, strong adhesion, and good biocompatibility. Dopamine-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…It was found that the N + content on the smooth surface of the polyurethane membrane (20.19%) was much more than that on the rough surface (15.12%), while the CO content was lower. These results indicated that the smooth surface had more quaternary ammonium salt groups and the rough surface had more dopamine groups (phenol hydroxyl oxidizes to quinone 42 ). This spontaneous microphase separation depends on the different migration of functional segments between the Gemini QAS and LDA.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…It was found that the N + content on the smooth surface of the polyurethane membrane (20.19%) was much more than that on the rough surface (15.12%), while the CO content was lower. These results indicated that the smooth surface had more quaternary ammonium salt groups and the rough surface had more dopamine groups (phenol hydroxyl oxidizes to quinone 42 ). This spontaneous microphase separation depends on the different migration of functional segments between the Gemini QAS and LDA.…”
Section: Resultsmentioning
confidence: 89%
“…These results indicated that the smooth surface had more quaternary ammonium salt groups and the rough surface had more dopamine groups (phenol hydroxyl oxidizes to quinone 42 ). This spontaneous microphase separation depends on the different migration of functional segments between the Gemini QAS and LDA.…”
Section: Synthesis and Characterization Of Polyurethane Membranesmentioning
confidence: 89%
See 1 more Smart Citation
“…What's more, they are non-toxic in vitro and in vivo (Stakleff et al, 2013). Zhao et al (Zhao et al, 2021) prepared a rapid in situ gelling of mussel polyurethane adhesives (MPUAs) under mild conditions, which showed good biocompatibility and strong adhesion to complex wounds. Faxing Zou et al (Zou et al, 2022) prepared a novel tissue adhesive composed of L-arginine, degradable polyurethane (DLPU) and GelMA for wound repair.…”
Section: Polyurethanementioning
confidence: 99%
“…Biomedical materials are used in trauma approaches to replace or restore the anatomic structure and function of damaged or missing tissues following any injury or disease by combining the topographical cues of biomaterials with cells or bioactive molecules (Tan et al, 2021). Bio-glue intended for trauma repair are often derived from particular extracellular matrix (ECM) molecules [e.g., fibrin (Kalsi et al, 2017), collagen (Schiele et al, 1992), hyaluronic acid (Luo et al, 2020)], or other natural polymers [e.g., gelatin/alginate (Song et al, 2022), chitosan (Lu et al, 2018)] or synthetic polymers [e.g., cyanoacrylate (Carvalho et al, 2021), polyurethane (Zhao et al, 2021), polyethylene glycol (Privett et al, 2021)]. While both natural and synthetic polymers are widely utilized as tissue adhesives, the use of ECM bio-glue is rarely seen (Nishiguchi and Taguchi, 2021;Yazdanpanah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%